INTEGRATIVES AS A FORM OF PERSONNEL TRAINING IN THE CONTEXT OF IMPLEMENTATION OF A NATIONAL PROJECT “LABOR PRODUCTIVITY AND EMPLOYMENT SUPPORT” - V. L. Popov; T. V. Aleksandrova (Вестник университета)
The issue of choice of the form of conducting classes within the framework of personnel training at industrial enterprises participating in the implementation of the national project “Labor productivity and employment support” has been studied. In the process of staff training, it is necessary to ensure an interdisciplinary approach to the formation of educational programs and take into account significant restrictions on the time and cost of training, which are provided within the framework of this national project. In such conditions, the most appropriate form of conducting classes with employees of enterprises participating in the national project becomes integratives, which are the union of several academic disciplines using action learning technologies. In the course of the study, a comprehensive model of personnel training using integratives was established, tested at the enterprises participating in the national project “Labor Productivity and Employment Support” in the Perm Territory and also the problems that arise during integrative classes and ways to solve them have been defined. The results of the study can be used to draw up programs and training plans for personnel of enterprises implementing the national project “Labor Productivity and Employment Support” in the regions of the Russian Federation.